2011 Fourth International Conference on Intelligent Computation Technology and Automation 2011
DOI: 10.1109/icicta.2011.328
|View full text |Cite
|
Sign up to set email alerts
|

Research on Optimized Fertilization for Filling Type Flue-cured Tobacco Based on Partial Least -squares Regression

Abstract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… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In order to obtain a more precise relationship between the glass artefacts and the three types of information, the significance test P-Value (later referred to as P) [1] was obtained using 2 χ , considering P>0.05 as a strong correlation between information and artefacts, and otherwise a weak correlation between information and artefacts. The results of the Person 2 χ test showed that the significance test P was greater than 0.05 for glass artefacts and ornamentation, and for glass artefacts and color, so the original hypothesis that glass artefacts and ornamentation and color are both independent is accepted.…”
Section: Modeling Solution 31 Person Testmentioning
confidence: 99%
“…In order to obtain a more precise relationship between the glass artefacts and the three types of information, the significance test P-Value (later referred to as P) [1] was obtained using 2 χ , considering P>0.05 as a strong correlation between information and artefacts, and otherwise a weak correlation between information and artefacts. The results of the Person 2 χ test showed that the significance test P was greater than 0.05 for glass artefacts and ornamentation, and for glass artefacts and color, so the original hypothesis that glass artefacts and ornamentation and color are both independent is accepted.…”
Section: Modeling Solution 31 Person Testmentioning
confidence: 99%